Cuidados De Enfermería En Personas Con Quemaduras En Cuidado Crítico (2021)
The nursing care provided to the patient must be complete and comprehensive as their being, therefore, there are various models of care from different nurses who provide us with their different points of view, to guide us on how to provide the different care that the patient needs. patient. For this reason, a detailed integrative review of various articles was carried out, using keywords in English, Portuguese and Spanish in different databases with updated information that is within the period from 2016 to the present, in which The activities that should be carried out to the patient with burns who are in critical care are mentioned in order to be able to organize them based on the Virgina Henderson model and as a result describe the nursing care that is provided to these patients according to their altered needs.